Penerapan Electre Pada Biji Kopi Berkualitas PT. Arvis Sanada Sanni Indonesia - Wira Apriani (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2019)
Coffee beans are the basic ingredient for PT. Arvis Sanda Sanni Indonesia. Export coffee beans supplied by various types of suppliers. The selection of export-quality coffee beans is carried out by the company only by looking at the seed sample data examined by the company. In this case the selection of export quality coffee beans seems manual and takes a long time. The design of decision support system applications in determining export-quality coffee beans using the method of Elimination Et Choix Traduisant la Realite (ELECTRE) method which takes criteria data based on general requirements, special requirements and coffee defect value of the company is expected to overcome the problems at PT. Arvis Sanda Sanni Indonesia. The final result expected from this decision support system application is information in the form of reports about the quality of the best exported coffee beans sorted by the data calculated on the system so that the best export coffee beans can be used as basic ingredients for the company.